Functional Dissection of the Periplasmic Domain of RcsD, the Phosphotransfer Protein of Escherichia Coli Rcs System - Dapour, Abdelraouf (AUC Knowledge Fountain, 2025)
Microbial resistance to antibiotics poses a major health threat worldwide, prompting the scientific community to dedicate considerable efforts toward understanding the molecular mechanisms underlying this resistance. The Gram-negative cell envelope serves as a formidable barrier to environmental stressors and numerous antimicrobials. In E. coli and other enterobacteria, the Rcs system (Regulator of capsule synthesis) is a crucial two-component signalling pathway that plays a critical role in maintaining the integrity of the bacterial envelope. One unique aspect of the Rcs system is the involvement of several auxiliary proteins in its signalling cascade. Among them, RcsD, an inner membrane 100 kDa protein, transfers phosphate from the histidine kinase (RcsC) to the cytosolic response regulator (RcsB). The cytosolic part of RcsD is essential for signalling due to its phosphotransferase function. However, RcsD also possesses a large periplasmic domain (69 kDa) whose roles remain unexplored. This work aims to elucidate the role of the RcsD periplasmic domain by examining the effects of its deletion and/or substitution on Rcs system activation and stress response. Enhancing our understanding of the Rcs system's signalling mechanism is anticipated to pave the way for the development of novel antibacterial agents. The main findings of this work suggest a dual role for the RcsD periplasmic domain depending on the presence or absence of stress signals. In the absence of stress signals, it assists IgaA in inhibiting system activation, thereby maintaining it at its minimal activation level. Conversely, in the presence of stress signals, an interaction occurs between RcsF and the RcsD periplasmic domain, facilitating signal transfer that is crucial for system activation.